Trachyrhizium urniformis n. g., n. sp., a Novel Marine Filose Thecate Amoeba Related to a Cercozoan Environmental Clade (Novel Clade 4). (10th May 2016) - Shiratori, Takashi; Ishida, Ken‐ichiro
Abstract: A novel cercozoan filose thecate amoeba, Trachyrhizium urniformis n. g., n. sp., was isolated from a marine sediment sample collected at Agenashiku Island, Okinawa, Japan. We performed light and electron microscopic observations, and a molecular phylogenetic analysis using the small subunit ribosomal RNA gene of the isolate. Cells of T. urniformis are spherical in shape and are covered by a thin theca possessing a wide rounded aperture. Branching and occasionally anastomosing filopodia with small granules emerge from the aperture. The granules are transported in the filopodia bidirectionally. Transmission electron microscopy showed that cells of T. urniformis possess nucleus with permanently condensed chromatin, Golgi apparatuses, microbodies, mitochondria with tubular cristae, and extrusomes. Several morphological and ultrastructural features of T. urniformis (the presence of thecae and nucleus with permanently condensed chromatin) show similarities with those of Thecofilosea. In a phylogenetic analysis, T. urniformis included in Thecofilosea with weak statistical supports and formed a clade with two sequences that constitutes a cercozoan environmental clade, novel clade 4. On the basis of morphological and ultrastructural information and the results of the phylogenetic analysis, we propose T. urniformis as a new member of class Thecofilosea.